Edukasi Pencegahan Kekerasan dalam Pacaran pada Remaja sebagai Bentuk “Tanda Bahaya yang Tersembunyi” di SMA Triguna Utama Syarif Hidayatullah - Aurellia Zayyani; Lucky Nurhadiyanto (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Dating violence among adolescents is a phenomenon that is often unnoticed and hidden behind relationships considered to be normal. Many adolescents get caught in unhealthy relationships due to a lack of understanding about boundaries and the types of violence that can occur in dating relationships, such as physical, verbal, emotional, and sexual abuse. Dating violence is often seen as part of the normal dynamics of a relationship, but it can have significant negative impacts on the mental and physical health of adolescents involved. This study aims to provide education on the importance of recognizing signs of dating violence and to encourage adolescents to build healthy, equitable relationships. Through educational activities, it is hoped that adolescents can increase their awareness of dating violence, understand the importance of boundaries, and gain the courage to take action if they or their partners experience violence. This education also aims to foster empathy, respect, and healthy communication skills between adolescent couples. The education provided includes information that helps adolescents recognize the different forms of violence and how to avoid them. It also emphasizes the importance of open communication and mutual support in relationships. With good communication skills, adolescents are expected to resolve conflicts constructively and keep their relationships positive. Values of equality and mutual respect in relationships are also introduced to ensure that both partners feel valued and respected. With a better understanding of healthy relationships, it is hoped that adolescents will be able to make better decisions in their relationships. Through ongoing education, dating violence can be prevented from an early age. This will allow adolescents to engage in safer, more respectful, and positive relationships, while reducing the negative effects of dating violence.